Developing Culture-Based Supplementary Reading Material for the Eighth Grade Students of Junior High School - Agustina Sianturi (Institut Agama Islam Negeri Palopo, 2021)
This study aimed to develop additional material in reading that is based on culture. In this study the subject is the eighth grade students of Junior High School Swasta Cendramata. The main objective in this research identified and reading issue that students faced. On describing this culture-based reading learning material to be developed so that students can have an attraction in reading with culture-based reading materials. In this study, using the development of culture-based reading materials adapted from the character Sugiono (2011) and based on good and correct reading criteria. The description of culture-based reading learning materials for 8th grade Junior High School Swasta Cendramata is described in 4 aspects, namely testing, content, language use and reading activities. This study uses a validity test which shows that the prototype is evaluated with good quality. The results of the research test were quite satisfying in improving students' reading learning, students enthusiastically showed a sense of curiosity and student activeness in reading culture-based reading materials in understanding how to read properly and correctly with culture-based reading materials..